Use of chemicals and biological products in Asian aquaculture and their potential environmental risks: a critical review - Andreu Rico; Kriengkrai Satapornvanit; Mohammad M. Haque; Jiang Min; Phuong T. Nguyen; Trevor C. Telfer; Paul J. van den Brink (Blackwell Publishing Asia Pty Ltd, 2025)
Over the past few decades, Asian aquaculture production has intensified rapidly through the adoption of technological advances, and the use of a wide array of chemical and biological products to control sediment and water quality and to treat and prevent disease outbreaks. The use of chemicals in aquaculture farms has raised environmental concerns owing to their potential impacts on downstream aquatic ecosystems. Currently little is known about the environmental fate and effects of the chemicals used in Asian aquaculture. Consequently, we reviewed recent information on the use of chemical and biological products in the most important Asian aquaculture producing countries and briefly summarize their main potential environmental impacts. We provide an overview of the main factors controlling the use of these chemicals and describe the international risk assessment guidelines available for aquaculture chemicals. Finally, data gaps and research needs for their implementation in Asian countries are discussed. Our review aims to form a basis for developing environmental risk assessment studies of the chemicals used in Asian aquaculture.